2002
DOI: 10.5172/conu.13.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Reservoirs of MRSA in the acute hospital setting: A systematic review

Abstract: The aim of this systematic review was to critically analyse the literature and present the best available evidence relating to the significance of environmental factors, including equipment, in the transmission of methicillin resistant Staphylococcus aureus (MRSA) to hospitalised patients. Despite an extensive literature search only twenty studies that met the inclusion criteria were identified and analysed. There is evidence that the equipment and the inanimate environment are common reservoirs of MRSA, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…[25][26][27][28][41][42][43][44][45][46] Using an intraoperative model of stopcock contamination, [12][13][14] we have shown that several bacterial reservoirs contribute to bacterial cross-contamination and, in fact, are intricately related. We have also shown that these reservoirs harbor unique subsets of major bacterial pathogens that can contribute to postoperative infection development.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][41][42][43][44][45][46] Using an intraoperative model of stopcock contamination, [12][13][14] we have shown that several bacterial reservoirs contribute to bacterial cross-contamination and, in fact, are intricately related. We have also shown that these reservoirs harbor unique subsets of major bacterial pathogens that can contribute to postoperative infection development.…”
Section: Discussionmentioning
confidence: 99%
“…2004, Cimolai 2008, Dancer 2009), suggesting that transmission of HCAIs by this route is plausible. Griffiths et al. (2002) systematic review found that over half of the inanimate objects in the hospital environment were not microbiologically clean, and Oie et al.…”
Section: Discussionmentioning
confidence: 99%
“…Shared equipment can act as a vehicle by which cross transmission occurs and can cause infections [19]. One systematic review [13] found that over half of the inanimate objects such as those previously listed were not microbiologically clean when swabbed and another study [21] suggests extensive contamination of MSSA and MRSA in the hospital environment. Poor environmental hygiene has been associated with transmission of pathogens and causing HCAIs [4,11] and it is for these reasons that although we recognize that just because microorganisms are present in the environment it does not always mean that these cause HCAIs, but it does warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%